Cancer‐related genetic changes in multistep hepatocarcinogenesis and their correlation with imaging and histological findings. Issue 9 (30th June 2020) - Muraoka, Masaru; Maekawa, Shinya; Suzuki, Yuichiro; Sato, Mitsuaki; Tatsumi, Akihisa; Matsuda, Shuya; Miura, Mika; Nakakuki, Natsuko; Shindo, Hiroko; Amemiya, Fumitake; Takano, Shinichi; Fukasawa, Mitsuharu; et al.
Abstract : Aim: The landscape of cancer‐related genetic aberrations in hepatocellular carcinoma (HCC) has gradually become clear through recent next‐generation sequencing studies. However, it remains unclear how genetic aberrations correlate with imaging and histological findings. Methods: Using 117 formalin‐fixed paraffin‐embedded specimens of primary liver tumors, we undertook targeted next‐generation sequencing of 50 cancer‐related genes and digital polymerase chain reaction of hTERT . After classifying tumors into several imaging groups by hierarchal clustering with the information from gadoxetic acid enhanced magnetic resonance imaging, contrast‐enhanced computed tomography, contrast‐enhanced ultrasound, and diffusion‐weighted imaging magnetic resonance imaging, the correlation between genetic aberrations and imaging and histology were investigated. Results: Most frequent mutations were hTERT (61.5%), followed by TP53 (42.7%), RB1 (24.8%), and CTNNB1 (18.8%). Liver tumors were classified into six imaging groups/grades, and the prevalence of hTERT mutations tended to increase with the advancement of imaging/histological grades ( P = 0.026 and 0.13, respectively), whereas no such tendency was evident for TP53 mutation ( P = 0.78 and 1.00, respectively). Focusing on the mutations in each tumor, although the variant frequency (VF) of hTERT did not change ( P = 0.36 and 0.14, respectively) in association with imaging/histological grades, TP53 VF increased significantly ( P = 0.004 and <0.001, respectively). In multivariate analysis, stage III or IV (hazard ratio, 3.64; P = 0.003), TP53 VF ≥ 50% (hazard ratio, 3.79; P = 0.020) was extracted as an independent risk for recurrence in primary HCC patients. Conclusions: Increased prevalence of hTERT mutation and increased TP53 mutation VF are characteristic features of HCC progression, diagnosed with imaging/histological studies.